Who’s Afraid of the Goddess? Leopard’s Tale, Menopausal Syndrome: Terms of Debate within Archaeology - Carta, Arianna (Studia mythologica Slavica, 2022)
This article presents an insight into archaeological disputes around female Neolithic figurines, starting with a historical overview of main academic interpretations of the figurines. Furthermore, it introduces feminist approaches in archaeology related to figurines, showing how androcentric bias has undermined theories and methodologies. Çatalhöyük case-study serves as an example of contrasting narratives. The article argues that academic devaluation of Marija Gimbutas’ work within contemporary archaeology can be considered a litmus test which show the pervasiveness of gender bias in this disciplinary field. Among peculiar arguments against Gimbutas’ theories, there are: menopause syndrome, gynocentric agenda, and reverse sexism, all of which show how the archaeologists have focused on personal attacks rather than on serious academic discussion. In the end, all those rhetoric strategies have shifted scholars’ attention from the main issue which is rarely addressed: why is it that the Neolithic period is dominated by female figurines?